Predation by the Pebas four-eyed opossums Philander pebas on the toad Rhinella margaritifera in the west Brazilian Amazon - Negreiros Almeida, Marllus Rafael; Lima da Fonseca, Wirven; Medeiros Borges, Luiz Henrique; Sérgio Bernarde, Paulo (Therya Notes, 2024)
Species of Philander occur in tropical and subtropical forests. Some species have a diet consisting of arthropods, the species within the genus are considered opportunistic vertebrate predators. Information about the natural history, ecology, and behavior of this genus is still scarce. Here, we present the first documented case of predation on the Rhinella margaritifera by Philander pebas in the Amazonian floodplain forest. The observation documented here was made during fieldwork in a trail located in the Area de Relevante Interesse Ecológico Japiim-Pentecoste, of Cruzeiro do Sul, Acre, Brazil. We photograph the records using camera with the help of lighting lanterns. We encountered 1 specimen of P. pebas moving through a tangle of lianas and palm leaves, we observed the opossum with Rhinella margaritifera securely held in its mouth. The toad was gripped dorsally by the widest part of its head and ventrally by part of its neck, encompassing the parotoid glands. We noticed that R. margaritifera in its mouth was alive and displayed a defensive behavior known as "puffing up the body". Remarkably, the opossum displayed no apparent signs of toxin effects while grasping the toad near its parotoid glands. These findings challenge conventional assumptions about the toad's defense mechanisms against predators. Our record expands the understanding of predator-prey interactions in the Amazonian the significance of further research to unravel the dynamics of these novel interactions between opossums and venomous amphibians.